What is Different about International Lending? - Chowdhry, Bhagwan (Review of Financial Studies, 1991)
[An attempt is made to explain how enforceability is achieved in international debt contracts. Each bank announces the policy of denying credit to borrowers who default and chooses to adhere to it to maintain its reputation of being a tough bank to discipline its other borrowers. Loans are made by syndicates of banks in order to make the penalty for default severe enough so borrowers would choose not to default voluntarily. The model predicts that the interest rate charged on loans is smaller for the larger borrowers. Also, for any given borrower, the interest rate may fall after each successive default.]